COMPARISON OF NEONATAL APGAR SCORES AND PATIENT SATISFACTION LEVELS IN SPINAL VERSUS GENERAL ANESTHESIA IN ELECTIVE CESAREAN SECTIONS - Naseer, Syed Khurram; Ali, Aijaz; Feroz, Shizan Hamid; Danish, Dr; Sohail, Amir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare patients undergoing cesarean section under spinal and general anesthesia in terms of neonatal APGAR scores and patient satisfaction. Study Design: Comparative cross-sectional study. Place and Duration of Study: Departments of Anesthesia and Gynecology and Obstetrics, Combined Military Hospital Peshawar, for six months from Mar to Aug 2019. Methodology: In this study, 120 females with a singleton pregnancy of 36-40 weeks, and requiring a non-emergency elective cesarean section were enrolled through consecutive sampling in the study. The patients were randomly allocated into two equal groups of 60 women each through random table numbers. Group A received spinal anesthesia and group B general anesthesia. APGAR score was assessed at 5 minutes after delivery, and score of ≥7 was taken as satisfactory. Patient’s satisfaction level regarding anesthesia was recorded on a visual analogue scale of 0 (extremely unsatisfied) to 10 (completely satisfied), and score of ≥7 was taken as satisfactory. Results: Women receiving general anesthesia were more satisfied as compared to receiving spinal anesthesia (95% vs. 78.3%; p-value 0.007). There was no significant difference in terms of APGAR scores in general anesthesia and spinal anesthesia (83.33% versus 90%; p-value 0.283). Conclusion: After an elective caesarean section, more mothers were satisfied after receiving general anesthesia as compared to spinal anesthesia. However, both types of anaesthesia were found to be equally safe for babies born in terms of APGAR scores at 5 minutes.